KUALITAS PELAYANAN DAN HARGA JASA TRANSPORTASI TERHADAP KEPUASAN PENUMPANG PADA PT AYU TRANSPORT SUNGAI PENUH - Indra Budaya (Institut Agama Islam Negeri Kerinci, 2022)
Purpose: To find out whether the Quality of Service and the Price of Transportation Services on Passenger Satisfaction at PT. Ayu Transport Sungai Penuh. Design/methodology/approach: This research is a causality descriptive study which belongs to quantitative research. The population of this study includes consumers, namely the passengers from PT. Ayu Transport Sungai Penuh whose number is unknown. The sampling method used accidental sampling technique. While the data analysis tool is using multiple linear regression. Findings: The results of this study reveal that either partially or simultaneously Service Quality and Price have an influence on service user satisfaction. Research implications: The results of this study are able to provide an overview for transportation service entrepreneurs to always pay attention to the quality of service and prices offered to create customer satisfaction